Alkaline phosphatase activity and immunoglobin concentration in in-vitro uterine flushings of buffaloes (Buba/us bubalis) - PROMOD, K; MAHMOOD, S; TELANG, A G; SINGH, R; BISHT, G S (The Indian Journal of Animal Reproduction, 2023)
Alkaline phosphatase activity and immunoglobulin concentration during follicular phase, luteal phase (early, mid and late), inactive ovarian stage and infected uterine flushing in-vitro was studied in buffalo uteri (n=SS) collected from local abattoir. The alkaline phosphatase activity varied significantly (P<0.05) between two uterine horns during early and late-luteal phase, however, the difference was non-significant during other stages. On the other hand, immunoglobulin concentration was nonsignificant between two uterine horns at all the stages. Both alkaline phosphatase activity and immunoglobulin concentration were significantly (P<0.01) higher in infected compared to other stage uterin.: flushings . Thus, in conclusion, these two parameters simultaneously could be used as an indicator of sub-clinical inflammatory conditions.